Experiences of antenatal care among pregnant adolescents at Kanyama and Matero clinics in Lusaka district, Zambia - Bwalya C. Bwalya; Doreen Sitali; Kumar Sridutt Baboo; Joseph M. Zulu (BMC, 2018)
Abstract Background Adolescent pregnancy is among the many public health concerns not only in Zambia but also in other parts of the world. Exploring pregnant adolescents' experiences of antenatal care may help to identify specific problems and the contextual relevant strategies to improve the access to antenatal care. The purpose of this study was to explore and describe the lived experiences of antenatal care among pregnant adolescents aged between 12 to 19 years old at Kanyama and Matero Referral Clinics in Lusaka district of Zambia. Methods This was a qualitative study which used in-depth interviews to collect data. Maximum variation sampling technique was used to select 12 pregnant adolescents of 12 to 19 years age range that attended antenatal care. Data were analysed thematically with the help of Nvivo software version 10. Results The study revealed that the adolescents experienced positive and negative antenatal care. While there were some reported cases of caring and friendly health care providers and older pregnant women, there were also reported cases of poor attitudes and behaviours by the older pregnant women and health care providers towards the adolescents. In addition, other issues that were reported by the adolescents were the opening hours for the health facilities which was not favourable to all adolescents and the lack of specific spaces for adolescents as well as inadequate privacy and confidentiality. Some solutions were suggested to overcome some of the problems such as reducing the waiting hours or time for consultations at the clinic and to have specific rooms or spaces for pregnant adolescents at the clinic. Conclusion Appropriate interventions targeting pregnant adolescents with emphasis on making antenatal care services more adolescent friendly may improve the quality of and accessibility of antenatal services. The adolescent friendly antenatal services should integrate health promotion activities aimed at sensitising elderly women within the health facilities on the importance of supporting pregnant adolescents.